Application of Traditional Chinese Medicine acupoint application combined with emotion regulation for patients with bronchial asthma (中医穴位贴敷联合情志护理在支气管哮喘患者中的应用) - ZHAO Le (赵乐) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) acupoint application combined with emotion regulation for patients with bronchial asthma. Methods Totally 66 patients with bronchial asthma were randomly divided into the observation group and the control group, with 33 cases in each group. All patients received routine treatment and nursing care, and those in the observation group were given TCM acupoint application combined with emotion regulation. The emotional status of patients before intervention, 1 month and three months after intervention were measures, and the treatment efficacy was compared between two groups. Results The Score of Self-Report Symptom Inventory Symptom Check-List90(SCL-90) was decreased in both two groups after intervention, and was lower in the observation group than that in the control group at 1 month and three months after intervention, respectively (P＜0. 05). The total effective rate in the observation group was higher than that in the control group (96. 97% vs. 78. 79%, P＜0. 05). Conclusion The TCM acupoint application combined with emotion regulation is effective to improve the emotional status of patients with bronchial asthma, and improve the clinical treatment efficacy. (目的 探讨中医穴位贴敷联合情志护理在支气管哮喘患者中的应用效果。方法 选66例支气管哮喘患者随机分为观察组和对照组, 各33例。对照组给予常规干预, 观察组在对照组基础上应用中医穴位贴敷联合情志护理干预。观察2组患者干预前、干预1个疗后和3个疗程后的心理情绪变化, 评估2组治疗效果。结果 干预后, 2组症状自评量表(SCL-90)量表评分均降低, 且观察组干预1个疗程和3个疗程后的SCL-90量表评分均对于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率96. 97% (32/33), 高于对照组的78. 79%(26/33), 差异有统计学意义(P＜0. 05)。结论 中医穴位贴敷联合情志护理可有效改善支气管哮喘患者心理情绪, 并提升临床疗效。)